DESIGN OPTIMIZATION OF EXTRACTION PROCEDURE FOR TERBIUM (III) BY SUPPORTED LIQUID MEMBRANE USING D2EHPA AND TOPO AS A CARRIER - SID AHMED ELHABIRI; MOHAMED A. DIDI* (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The extraction of terbium (III) from aqueous nitrate solutions with a supported liquid membrane was investigated using a mixture of di-(2-ethylhexyl phosphoric acid (D2EHPA) and tri-octyl phosphine oxide (TOPO) with a molar ratio 1/0.4. The mixture was dissolved in diethyl ether which served as a carrier. The hydrophobic polyvinylidene fluoride (PVDF) membrane was used as a solid support. SEM images and FTIR spectra showed that the PVDF membrane was modified after impregnation. The sorption process followed a pseudo-second-order kinetics. 8.29 mg∙g-1 was extracted using a supported liquid membrane (SLM). The mixture D2EHPA / TOPO (1/0.4) presented a synergistic effect. The influence of the ionic strength, stirring rate, extraction time, and the interactions between them on the extraction yield of terbium (III) ions was investigated using the factorial designs. The analysis of variance (ANOVA) was used to show the relative importance of the extraction process parameters. Student’s t-test to the results of the factorial plane 33, with 30 runs for terbium (III) extraction, showed that the stirring rate in the studied ranges was statistically important. The amount of Tb (III) extracted after 12 cycles was 73.624 mg∙g-1.